B is for Bauhaus : an A-Z of of the modern world - Sudjic, Deyan (Particular Books, 2014)
This book is not a dictionary, though it tells you all you need know about everything from Authenticity to Zips. It's not an autobiography, though it does offer a revealing and highly personal inside view of contemporary culture. It's an essential tool kit for understanding the modern world. It's about what makes a Warhol a genuine fake; the creation of national identities; the mania to collect. It's also about the world seen from the rear view mirror of Grand Theft Auto V; digital ornament and why we value imperfection. It's about drinking a bruisingly dry martini in Adolf Loo's American bar in Vienna, and about Hitchcock's film sets. It's about fashion and technology, about politics and art.-Publisher's description.